A comprehensive framework for feasibility of CCUS deployment: A meta-review of literature on factors impacting CCUS deployment. (May 2023) - Storrs, Kasper; Lyhne, Ivar; Drustrup, Rikke
Highlights: 22 reviews of CCUS literature are reviewed for CCUS challenges. The challenges are grouped into 18 factors in a framework of 7 overall categories. Technical and economic challenges are most widely presented. Key social aspects appear underrepresented in the meta-review. Abstract: Carbon capture, utilisation and storage (CCUS) has gained prominence as one of a suite of technologies needed for mitigating the urgent threat posed by climate change. Despite the significance of CCUS technologies to a multitude of climate mitigation scenarios, research has identified a series of challenges to deployment, ranging from cost overruns and technical failures to public opposition. Research has widely documented the range of techno-economic challenges impacting the feasibility of individual technologies. However, a growing body of research calls for the feasibility of CCUS to be assessed more holistically, with greater focus on systemic, societal and other non-technical issues. Through a meta-review of 22 recent multidisciplinary review papers on CCUS, we identify and explore a comprehensive set of challenges impacting CCUS deployment. The results show a continued focus on the techno-economic dimensions within literature. However, the meta-review also unfolds a series of issues receiving less attention in literature, from organisational and environmental challenges to issues of legitimacy. Overall, this paper contributes to a broader understanding of the critical challenges facing CCUS projects in the coming decade and provides a framework for a more holistic assessment of climate mitigation technologies such as CCUS.